Ridiculed that she wouldn’t succeed, Laili proves otherwise - Siti Nurfarmy, Ibrahim (UMPSA, 2023)
GAMBANG, 22 October 2023 - Insinuations that she will not succeed have become the spark for Nur Layli Wirman, 25, the daughter of a former tailor, Wirman Tengku Munaf, 61 and restaurateur, Afni Zakaria, 58, to prove people’s perception of her family is completely wrong.